Peningkatan Ketrampilan Wirausaha Muda dalam Pengelolaan Keuangan Bisnis Melalui Workshop dan Pendampingan Penyusunan Rencana Bisnis - Kevin H. Tupamahu; Aprilia Lerrech (Jurnal Pemimpin Bisnis Inovatif, 2024)
This article explains the thematic community service program which is a form of activity that provides learning experiences for each student to be able to adapt to the community environment with all the problems that occur. I am one of the KKN students located in Jattinangor sub-district, Sumedang Regency, West Java. Young entrepreneur skills development program aimed at improving abilities in managing business finances. This program uses an intensive workshop approach and personal assistance in preparing a business plan. This training method is designed to provide an in-depth understanding of business financial management and skills in designing effective business plans. Through a series of training and mentoring sessions, entrepreneurs and prospective entrepreneurs are given the opportunity to understand the basic concepts of business finance, identify business financial needs, and formulate strategies to achieve financial goals. Program evaluations show significant improvements in business financial understanding and skills as well as success in designing realistic and targeted business plans. With workshops and mentoring, it is hoped that you can improve your skills in starting a business or running a business.